PEMASARAN SOSIAL POSYANDU LANSIA (Studi Kualitatif Wilayah Kerja Puskesmas Pudakpayung Kota Semarang) - Khusnia Widowati; Priyadi Nugraha Prabamukti; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2019)
Elderly Posyandu (Pos Pelayanan Terpadu) is a community-based health service to serve the elderly, whose process of formation and implementation is carried out by the community across the government and non-government sectors by focusing on promotive and preventive efforts. Elderly Posyandu at the working area of Pudakpayung Public Health Center had the lowest average number of visits in Semarang City, namely 16.8% indicating that there were still many elderly people who had not utilized Posyandu. The purpose of this study was to determine the 7P social marketing analysis needed by the elderly in the Pudakpayung Health Center area. This study uses a qualitative method. The research subjects were 11 Posyandu participants as the main informants and 4 triangulation informants, 2 cadres and 2 health center’s officers. The research subjects were obtained by purposive sampling method. The results of the study showed that based on 7P social marketing analysis, In the Product, packaging of the activities were considered less attractive and not all Posyandu has a scheduled physical activity. In Price variable, there are no significant obstacles in terms of costs, time, or physical discomfort. In the Place, location and duration of the Posyandu implementation is suit with the needs of the elderly. In Promotion, promotion through citizen meetings is the most effective strategy for the elderly to remember the Posyandu schedule. In the Process, there has been a good interaction between cadres and the elderly. In People, the quantity of cadres is considered sufficient but not all play an active role, while the quality of cadres is considered to be less evenly distributed because not all cadres receive training from the Health center. In Physical Evidence, all informants need a complete health services and supporting facilities  to increase the visits of elderly Posyandu.